Laparoscopic versus open hysterectomies in obese patients - El Shakhs, Soliman A.; Mohamed, Moharam A.; Shahin, Mahmoud A.; Eid, Ahmed M. (International Surgery Journal, 2018)
Background: Hysterectomy is one of the most frequently performed surgical procedure. Though there are three approaches in hysterectomy (open, vaginal and laparoscopic), still there are controversies regarding the optimal route for performing it. Methods: This prospective comparative study included 42 obese patients subjected for pan-hysterectomy as a treatment. The forty-two patients were allocated into two groups: group (A) subjected to laparoscopic pan-hysterectomy, group (B) subjected to open pan-hysterectomy. Results: There was significant difference between the two groups regarding mean operative time, blood loss, analgesic requirements and hospital stay, while no significant difference regarding intra-operative complications. Conclusions: Laparoscopic hysterectomy in obese patients has emerged as a viable, safe and better alternative to open hysterectomy amongst appropriately trained surgeons.